Easter and Covid-19 Pandemic in Indonesia: A reflection Through the Allegoric-Typological Approach - MAYASTUTI, Erlin; MARGARETA, Fanni; YEREMIA; PATANDEAN, Yohanes Enci (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2023)
This article examines the observance of Easter Day concerning the COVID-19 pandemic in Indonesia. For this reason, an allegorical-typological approach is used to explain the theological meaning of the Easter celebration and the pandemic situation, both of which have spiritual meanings that need to be raised to the surface to become a reflection of the faith of God’s people. Easter celebrations provide a catalyst for people to renew their spirituality and reorganise various aspects of Christ’s followers’ lives. The COVID-19 pandemic has brought about a change in mindset and new habits of life for the world community, including believers. The research data collection uses the literature study method, and the discussion uses an allegorical and typological approach. The findings indicate that interpreting Easter during the COVID-19 pandemic in Indonesia, with all of its consequences, is a push to appreciate Christ’s work, which saves people from death and restores human relationships with God, others, and the environment, as well as providing directions for Christians to practise spiritual discipline. The results of this research are also a suggestion for every follower of Jesus Christ to apply for spiritual reinforcement.